Study of structural and mechanical properties of bases in the development of dental gel with combined composition - Yakovenko, Volodymyr; Orlenko, Dmytro; Vyshnevska, Liliia (ScienceRise: Pharmaceutical Science, 2019)
Aim. The development of the composition of the dental gel for the treatment of infectious and inflammatory diseases of the oral cavity, taking into account the physicochemical properties of the active pharmaceutical ingredients, namely the justification of the type and concentration of the gelling agent and other excipients. Methods. The determination of organoleptic characteristics, uniformity of gel samples, pH of aqueous extract, and structural viscosity index was carried out according to the methods of the State Pharmacopoeia of Ukraine. Rheological studies were carried out using a rotational viscometer of the rotating type BROOKFIELD DV-II + PRO (USA) with a coaxial cylinder system. Results. In order to choose the optimal composition of the gel base, experimental samples with various gelling agents were developed (Carbopol 974P, Carbopol 934P, Carbopol Ultrez 10, xanthan gum, sodium alginate, sodium carmellose) and their organoleptic characteristics, structural viscosity and colloidal stability were studied. The physicochemical and rheological studies that were carried out, allowed us to conclude that it is rational to use the Carbopol Ultrez 10 gel former at a concentration of 1.1 %. When choosing neutralizing agents, sodium hydroxide and trometamol were used in the studies. According to the results of studies, sodium hydroxide at a concentration of 0.32 % was selected as a neutralizer, which provides maximum, stable viscosity in the pH range from 5.0 to 7.0. Concusions. The composition of the basis of a dental gel for the treatment of infectious and inflammatory diseases of the oral cavity has been developed: Carbopol Ultrez 10 - 1.1 %, sodium hydroxide solution 10 %–0.32 %